Comparison of efficacy and toxicity of bevacizumab, endostar and apatinib in transgenic and human lung cancer xenograftzebrafish model. Issue 1 (December 2018) - Jin, Yinghua; Wei, Lingxiao; Jiang, Qiuying; Song, Xiaowei; Teng, Chong; Fan, Chengjuan; Lv, Yanju; Liu, Ying; Shen, Weixi; Li, Li; Huang, Dayong; Xin, Tao
Abstract The poor prognosis in non-small-cell lung cancer has driven the development of novel targeted therapies. Vascular endothelial growth factor is the most potent force in mediating tumor angiogenesis, and many angiogenesis inhibitors have been developed for oncology treatment. We performed a study to characterize the efficacy, safety and tumor suppression of three lung cancer related anti-angiogenic drugs (bevacizumab, endostar and apatinib) using transgenic zebrafish embryo and human lung cancer xenotransplantation model. All three drugs demonstrated remarkable angiogenesis and tumor inhibition effect in the zebrafish model, within the nonlethal dose range. Endostar and bevacizumab showed competitive anti-tumor efficacy. The anti-tumor performance of apatinib was hamstrung by its elevated toxicity at 35 °C. The addition of pemetrexed to anti-angiogenesis therapy had no obvious additional benefit in tumors.